Building Credibility and Consensus as Newly-Tenured or Junior Faculty Chairs - Carmen T. Skaggs; Jennifer Eimers (Academic Chairpersons Conference Proceedings, 2015)
Participants will explore the challenges that newly-tenured or junior faculty department chairs may face. Representing a small, private college and a regional comprehensive university, our panelists will offer recommendations for building credibility and consensus within the department even when there may be a gap of age and/or experience between the chair and faculty.
Keywords: credibility; consensus; experience; strategy; management